A sociological perspective on hierarchies in educational institutions - Argaman, Einav (Emerald Publishing Limited, 2022)
Hierarchy within the educational setting is a topic underrepresented in the existing literature, yet an area rich with unique social characteristics and particular challenges. A Sociological Perspective on Hierarchies in Educational Institutions traces hierarchical origins, differentiating between their types and discussing related terms such as positioning, social stratification, and central root vs. rhizomatic structure to offer a comprehensive complex exploration. By presenting the circumstances under which hierarchies flourish or diminish, Einav Argaman provides illustrative examples for the ways in which inter- and intra-institutional hierarchies are constructed and displayed, and points to existing and future directions that hierarchies in educational institutions may take. Offering a step-by-step guide to identifying and changing hierarchical relationships in schools, colleges and universities, A Sociological Perspective on Hierarchies in Educational Institutions bridges the gap between theory and practice. Drawing together research from different perspectives without losing comprehensiveness, accuracy, and in-depth coverage of hierarchy and educational institutions, this work is a novel contribution to Organizational Studies. The interdisciplinary scope of Argaman's study spans across multiple academic fields, including education, sociology, organization studies, management, curriculum studies, linguistics, and architecture. It is an accessibly written resource for researchers, academics, and teaching.
Keywords: Educational sociology.; Organizational sociology.; Public institutions -- Social aspects.; Hierarchies.; Education / Philosophy, Theory & Social Aspects.; Moral & social purpose of education.; elektronické knihy; electronic books